ISLAM DAN BUDAYA MASYARAKAT (STUDI TRADISI BARITAN DESA WANARATA PEMALANG) - Rias Iffa Pramesthi; Rofiqotul Aini (FiTUA: Jurnal Studi Islam, 2022)
This article examines the Islamic values ​​contained in the baritan tradition in Wanarata Village. This study uses ethnographic research using qualitative descriptive methods. The data collection method used is the method of observation, interviews, and documentation. The results of the study can be concluded that baritan is a form of salvation tradition which is usually carried out every month of Suro or Muharam to ask for welfare and also as a form of gratitude to God. This baritan tradition itself contains several Islamic values ​​which are directly or indirectly contained in a series of events, such as theological values, togetherness values, cultural values, aqidah values, akhlaqul karimah values, Islamic esoteric symbols, etc.